2015
DOI: 10.1186/s12939-015-0148-0
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health in the Mixtec and Zapotec community in Ventura County, California

Abstract: IntroductionThere are an estimated 165,000 indigenous Mexicans living in California, including Mixtec and Zapotec immigrant farm workers. Because many of these immigrants speak only their native non-written languages, there is little information about the needs of this community. An academic-community partnership research team developed a survey to assess basic needs that are known to be social determinants of health in the Mixtec and Zapotec community in Ventura County.MethodsIn summer 2013, Spanish-Mixteco a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…We noticed that the health access for children was better than that for adults. This is in agreement with other studies where adults reported that they prefer to seek medical attention for their children rather than for themselves [12].…”
Section: Discussionsupporting
confidence: 93%
“…We noticed that the health access for children was better than that for adults. This is in agreement with other studies where adults reported that they prefer to seek medical attention for their children rather than for themselves [12].…”
Section: Discussionsupporting
confidence: 93%
“…The bond between TB patient and the professional and health services is directly related to the continuity of care (4) and success of the treatment. In the search for solutions to the problem of TB in the homeless population, professional subjects believe that action on the social determinants understood as better social conditions such as housing, education, recreation, sanitation, employment and change of lifestyle can be facilitators for reducing the disease in this group (18)(19) . The linguistic remark 'challenge' indicates the need for change and new www.ee.usp.br/reeusp Experience of health professionals in care of the homeless population with tuberculosis perspectives of health care, such as intervention in all of the health production chain: health promotion, disease prevention, surveillance and rehabilitation, in addition to medical care and medication (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these promotoras are now employed by local clinics to serve as interpreters and navigators for indigenous patients. MICOP and the University of California Los Angeles partnered in 2011 to enhance the capacity for health promotion in the indigenous community in Ventura County [7, 8]. The study we discuss here focused on understanding access to care and navigation of health care services among indigenous women.…”
Section: Introductionmentioning
confidence: 99%